Big picture initiatives in bleeding disorders. (6th May 2022) - Rauch, Antoine; Valentino, Leonard A.; Mills, Kevin; Witkop, Michelle L.; Santaella, Maria E.; DiMichele, Donna; Recht, Michael; Susen, Sophie
Abstract: Introduction: The inherited bleeding disorders (IBD) community has witnessed significant therapeutic advances recently, yet important gaps persist, particularly for those with rare disorders and historically underserved populations. Aims: ‐ To create a national research blueprint agenda, led by the National Hemophilia Foundation (NHF), enhancing patient‐centric principles, accelerate research progress and address important gaps in care. ‐ To review critical gaps that remain to be addressed in women with IBDs, who face specific bleeding challenges. Methods: The NHF research blueprint research agenda was defined by input from across the community, including caregivers and patients who are considered subject matter experts of their IBD, research leaders, allied health professionals and specialists, and representatives of the biopharmaceutical industry. In addition, two medical experts in the field of IBDs performed a comprehensive review to address the knowledge gaps in women with IBDs. Results: Two foundational principles of the NHF blueprint are: (1) it must deliver on key issues that significantly impact the lives of those affected by IBDs, and (2) the priorities defined are relevant and actionable aimed to achieve health equity among all those affected by IBDs. A multidisciplinary approach is necessary for an optimal management of puberty, transition to adulthood and pregnancy. Even if strict guidelines are followed, recent studies show that women with IBDs are still facing a high burden. Conclusion: NHF blueprint will be issued in 2022. A specific research agenda is needed in women with IBDs to further improve their management and quality of life. Abstract :